Dual‐Ligand Functionalized Ag2S Quantum Dots for Turn‐On Detection of Lead (II) Ions in Mineral Samples Based on Aggregation‐Induced Enhanced Emission. Issue 17 (30th April 2021) - Cheng, Shasha; Hou, Dongyan; Li, Chen; Liu, Shu; Zhang, Cuiling; Kong, Qianqian; Ye, Mingqiang; Wu, Shan; Xian, Yuezhong
Abstract: Lead ion (Pb 2+ ) is considered as one of the most toxic elements because it damages human health and pollutes the environment. Therefore, it is of great significance to develop convenient assays for the detection of Pb 2+ with high sensitivity. A simple fluorescent probe for selective Pb 2+ sensing based on silver sulfide quantum dots (Ag2 S QDs) was developed in this work. The Ag2 S QDs with excellent fluorescence properties were synthesized without the need of oxygen‐free condition. In the presence of Pb 2+, the coordination between Pb 2+ with glutathione ligand modified on Ag2 S QDs could enhance the signal intensity of Ag2 S QDs via aggregation induced enhanced emission (AIEE). Thus, the Pb 2+ sensor was successfully developed based on a fluorescence turn‐on mechanism. The Pb 2+ sensor shows a linear detection range from 0.05–20.0 μM, and the detection limit is down to 15.5 nM. Furthermore, the constructed assay have been successfully applied for the detection of Pb 2+ in the mineral samples. The sensing system for Pb 2+ detection based 3‐MPA/GSH‐Ag2 S QDs has outstanding advantages, including fast response, high sensitivity, and easy operation. Therefore, it shows great potential in environmental detection. Abstract : We developed a simple fluorescent probe for Pb 2+ sensing in mineral samples based on silver sulfide quantum dots (Ag2 S QDs). In the presence of Pb 2+, the coordination between Pb 2+ with glutathione ligand on the surface of Ag2 S QDs could enhance the signal intensity of Ag2 S QDs via aggregation induced enhanced emission (AIEE).